Communication Strategies and Tactics as Key Points of Business Development - Machulska, Kateryna (Zeszyty Naukowe UPH seria Administracja i Zarządzanie, 2019)
The study of communication strategies and tactics occupies an important niche in strategic management. The relevance of this article lies in the fact that the interest of modern business administration science in the search for patterns and mechanisms of communication influence on the recipient is growing constantly. Communication strategies and tactics in the advertising of English-language web-recourses have been determined. We have defined two communication strategies for onlinestores slogans: 1) a strategy of encouraging the consumer to choose the appropriate goods or service; 2) a strategy of positioning the organisation in the market. Also various communication tactics, with the help of which those two strategies can be realised, have been described. They are: tactics of appeal to the consumer; tactics of target group indication; tactics of ambiguity/disambiguity of the expression, content and references; tactics of demonstration of the organisation's advantages and disadvantages; tactics of emphasizing competence, experience, traditions and values; tactics of goods and services naming; tactics of using the store's name. In this article we try to identify which of them is the most effective. The proposed versions are based on the results of linguistic interviewing.